2003
DOI: 10.1038/sj.onc.1206271
|View full text |Cite
|
Sign up to set email alerts
|

THAP1 is a nuclear proapoptotic factor that links prostate-apoptosis-response-4 (Par-4) to PML nuclear bodies

Abstract: Promyelocytic leukemia (PML) nuclear bodies (PML NBs) are discrete subnuclear domains organized by the promyelocytic leukemia protein PML, a tumor suppressor essential for multiple apoptotic pathways. We have recently described a novel family of cellular factors, the THAP proteins, characterized by the presence at their amino-terminus of an evolutionary conserved putative DNA-binding motif, designated THAP domain. Here, we report that THAP1 is a novel nuclear proapoptotic factor associated with PML NBs, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
145
0
6

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 144 publications
(154 citation statements)
references
References 49 publications
3
145
0
6
Order By: Relevance
“…Lifetime penetrance of this disorder is estimated to be approximately 60% with no sex differences identified 9 . The DYT6 gene (THAP1) consists of three exons and codes for the THAP1 protein 10,11 . THAP1 is a nuclear proapoptotic factor that potentiates tumor necrosis factor (TNF)-α-induced apoptosis and serum withdrawal-induced apoptosis 10 .…”
Section: Dyt6 Dystoniamentioning
confidence: 99%
See 1 more Smart Citation
“…Lifetime penetrance of this disorder is estimated to be approximately 60% with no sex differences identified 9 . The DYT6 gene (THAP1) consists of three exons and codes for the THAP1 protein 10,11 . THAP1 is a nuclear proapoptotic factor that potentiates tumor necrosis factor (TNF)-α-induced apoptosis and serum withdrawal-induced apoptosis 10 .…”
Section: Dyt6 Dystoniamentioning
confidence: 99%
“…The DYT6 gene (THAP1) consists of three exons and codes for the THAP1 protein 10,11 . THAP1 is a nuclear proapoptotic factor that potentiates tumor necrosis factor (TNF)-α-induced apoptosis and serum withdrawal-induced apoptosis 10 . Although many of the biological functions of THAP proteins apart from their involvement in apoptotic pathways remain unknown, various findings have confirmed that they play an important role in cell proliferation 10,11 .…”
Section: Dyt6 Dystoniamentioning
confidence: 99%
“…This motif, designated THAP domain or THAP zinc finger, defines a previously uncharacterized large family of cellular factors with more than 100 distinct members in the animal kingdom (6,7). We showed that the THAP domain of THAP1, the prototype of the THAP family (8), possesses zinc-dependent sequence-specific DNA binding activity and recognizes a consensus DNA target sequence of 11 nucleotides (THABS, for the THAP1 binding sequence) (7), considerably larger than the 3-4 nucleotides motif typically recognized by classical C2H2 zinc fingers (2,7). Interestingly, the consensus C2CH signature of the THAP domain was identified in the sequence-specific DNA-binding domain of Drosophila P element transposase, suggesting the THAP zinc finger constitutes a novel example of a DNA-binding domain shared between cellular proteins and transposons from mobile genomic parasites (6,9).…”
mentioning
confidence: 99%
“…This technique may also require a priori selection of infusion sites, and as such it is also a biased approach. Unfortunately, some of the most common dystonia genes code for proteins that function in a variety of processes important for cell signaling, stability, and maintenance [48,[77][78][79][80]. In these cases, finding a compound that inhibits a specific function of the protein of interest is likely to be difficult or even impossible.…”
Section: Alternative Approaches For the Generation Of Rodent Models Omentioning
confidence: 99%